Production practices and potentials for small ruminants In Punjab Province - IQUBAL, ARSHAD; MEHDI, SYED S; YOUNAS, MUHAMMED; AHMAD, FAYAZ (The Indian Journal of Animal Sciences, 2013)
This study was conducted in 7 districts of the Punjab, viz. Kasaur, Lakhore, Sheikhupura and Toba Tak Singh (zone I) and Bhakkar, Dera Ghazi Khan and Muzaffargarh (zone II), to evaluate various prospects and limitations regarding the production practices and potentials of small ruminants. The average costs incurred on ordinary housing, feeding, medication and labour were higher in zone I. Contrary to that the same were less in the districts of wne II, primarily due to the availability of more natural resources, conventional methods of feeding, treatment and lesser employment opportunities for the) labour oree. Similarly the average income received by the fanners from the sale of these animals and theirproducts was higher in zone I due to the demand ofÂ animals and their products in the urban markets, increased awareness and high economic status of the urban masses as compared to the rural livestock raisers in wne II. The results obtained from the present study provides a useful and reliable guideline for the farmers, beginners and policy makers to have an idea abou.t the running costs, and the extent of net profit obtained from the sale of sheep, goats and their products in the respective regions.